Cutaneous tuberculosis-management - Panchatsharam, Adithyan; Sundaramurthy, Revathy (International Journal of Research in Dermatology, 2023)
Since antiquity, people have been plagued by tuberculosis (TB), and its effects are likely older than recorded history. For many centuries, TB was the most significant human infection due to its devastating mortality and morbidity rates and global prevalence. In developed nations, there is less evidence of Mycobacterium tuberculosis infections as a result of improved socioeconomic status. In developing nations like India, it is still regarded as a significant cause of morbidity and mortality. Cutaneous TB occurs worldwide and it comprises only a small proportion of all cases of TB, but considering the high prevalence of TB in many developing countries like India these numbers become significant. Cutaneous TB is a form of extra pulmonary TB and is characterized by a spectrum of multiple distinct clinical and histopathological presentations. It is imperative that the treating dermatologist is aware of the varied manifestations of cutaneous TB which would significantly prevent the morbidity and complications. This review aims to discuss the epidemiology, clinical, histopathological features, diagnosis, differential diagnosis and treatment options, especially in the Indian context.